2021
DOI: 10.1021/acsnano.1c06973
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Interfacial Graphene Oxide Reduction by Liquid Metals: Application in Selective Biosensing

Abstract: Liquid metals (LMs) are electronic liquid with enigmatic interfacial chemistry and physics. These features make them promising materials for driving chemical reactions on their surfaces for designing nanoarchitectonic systems. Herein, we showed the interfacial interaction between eutectic gallium−indium (EGaIn) liquid metal and graphene oxide (GO) for the reduction of both substrate-based and free-standing GO. NanoIR surface mapping indicated the successful removal of carbonyl groups. Based on the gained knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 52 publications
(85 reference statements)
6
71
0
Order By: Relevance
“…To enhance the photothermal conversion efficiency of liquid GaNPs, a graphene nanosheet shell is utilized as a strong light absorber and photothermal conversion center in this work. , Conventional methods to synthesize NPs with a metallic core–graphene shell require the surface modification of a rigid core with positively charged functional groups as the first step to attract negatively charged graphene oxide (GO) sheets. , RGO forms by chemical reduction of the GO sheets by, for example, the addition of hydrazine hydrate , or thermal treatment with a H 2 –Ar gas mixture. , Such relatively complicated synthetic methods may limit the scale-up of the product, and most surfactants in the reactions are hard to be removed and toxic to cells, , which further brings safety hazards in the field of biological-related applications. Micro-sized LM droplets assembled with reduced GO sheets was developed by Baharfar et al Using the strong galvanic interaction between LM and GO, the core–shell structure was synthesized and applied to selective biosensing of dopamine, which is one of the most important neurotransmitters. In addition, it has been reported that LM-reduced GO core–shell structure showed great potential in electrochemical detection of heavy metal ions .…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the photothermal conversion efficiency of liquid GaNPs, a graphene nanosheet shell is utilized as a strong light absorber and photothermal conversion center in this work. , Conventional methods to synthesize NPs with a metallic core–graphene shell require the surface modification of a rigid core with positively charged functional groups as the first step to attract negatively charged graphene oxide (GO) sheets. , RGO forms by chemical reduction of the GO sheets by, for example, the addition of hydrazine hydrate , or thermal treatment with a H 2 –Ar gas mixture. , Such relatively complicated synthetic methods may limit the scale-up of the product, and most surfactants in the reactions are hard to be removed and toxic to cells, , which further brings safety hazards in the field of biological-related applications. Micro-sized LM droplets assembled with reduced GO sheets was developed by Baharfar et al Using the strong galvanic interaction between LM and GO, the core–shell structure was synthesized and applied to selective biosensing of dopamine, which is one of the most important neurotransmitters. In addition, it has been reported that LM-reduced GO core–shell structure showed great potential in electrochemical detection of heavy metal ions .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] They exhibit robust LM was mixed with metal oxides to form the new kind of LM composites. [24,25] However, examples that compositing LM with nonmetallic particles remain restricted to a few types of fillers and strict requirements for atmosphere conditions (quantities of oxygen to guarantee gallium oxide) and particle size (>100 µm). [19,26] Therefore, the solution that can expand the nonmetallic toolbox to modify LM with a more universal and friendly strategy is urgently desired but has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…8,13 Room-temperature liquid metal, on the other hand, is naturally exible, easy to form, has good stretching resistance, and is another popular material for the fabrication of exible microelectrodes. 14 However, to shape metal that exists in the liquid state, structures such as microchannels, 7,15,16 a printing mask, 17,18 a transfer mask, 19 or stickers are required to perform transfer printing or direct writing 20 to pattern liquid metal as microelectrodes. Masking approaches are usually employed in the printing-related fabrication of liquid metal microelectrodes where liquid metal is injected or transferred on so material like thin polymer lms, a high-surface-energy gold layer, paper, or PMA glue.…”
Section: Introductionmentioning
confidence: 99%